Mental and somatic health and pre- and post-migration factors among older Somali refugees in Finland. (August 2014) - Mölsä, Mulki; Punamäki, Raija-Leena; Saarni, Samuli I.; Tiilikainen, Marja; Kuittinen, Saija; Honkasalo, Marja-Liisa
Mental and somatic health was compared between older Somali refugees and their pair-matched Finnish natives, and the role of pre-migration trauma and post-migration stressors among the refugees. One hundred and twenty-eight Somalis between 50–80 years of age were selected from the Somali older adult population living in the Helsinki area ( N  = 307). Participants were matched with native Finns by gender, age, education, and civic status. The BDI-21 was used for depressive symptoms, the GHQ-12 for psychological distress, and the HRQoL was used for health-related quality of life. Standard instruments were used for sleeping difficulties, somatic symptoms and somatization, hypochondria, and self-rated health. Clinically significant differences in psychological distress, depressive symptoms, sleeping difficulties, self-rated health status, subjective quality of life, and functional capacity were found between the Somali and Finnish groups. In each case, the Somalis fared worse than the Finns. No significant differences in somatization were found between the two groups. Exposure to traumatic events prior to immigrating to Finland was associated with higher levels of mental distress, as well as poorer health status, health-related quality of life, and subjective quality of life among Somalis. Refugee-related traumatic experiences may constitute a long lasting mental health burden among older adults. Health care professionals in host countries must take into account these realities while planning for the care of refugee populations.